Paradigms in the Mental Lexicon: Evidence From German - van de Vijver, Ruben; Baer-Henney, Dinah (Frontiers in Communication, 2019)
Previous research showed that the mental lexicon is organized morphologically, but the evidence was limited to words that differ only in subphonemic detail. We investigated whether word forms that are related through morphology but have a different stem vowel affect each other's processing. We focused on two issues in two auditory lexical decision experiments. The first is whether the number of morphologically related word forms with the same stem vowel matters. The second is whether the source of similarity matters. Word recognition experiments have shown that word forms that are phonologically embedded and related through inflection speed up each other's recognition, suggesting the word forms are represented within one unit in the mental lexicon. Research has further shown that words that are related through derivation, but that are phonologically different, are affected in a different way than words that are related through inflection. We conducted two experiments to further investigate this. We used three subtypes of one inflectional class of German nouns, which allowed us to study different word forms with a phonological difference, while keeping the morphological relations among the word forms constant. All of these nouns have a plural form that ends in a -ə. They differ in the distribution of front and back vowels in the singular, plural, and diminutive. This allows us to investigate the question whether word forms with different phonemes are processed differently with regard to (a) the number of word forms that share a vowel, and (b) the source of the similarity among the word forms; is the processing among word forms related through inflection different from the processing of word forms that are related through derivation? We found that nonces that are based on word forms with a fronted vowel are mistaken for words when they resemble words in the word family, but not when they are unrelated to words in the word family. This shows that morphological effects in word auditory recognition studies are also found when the word forms differ in a full phoneme. We argue that this can be captured with a network representation, instantiated as a frame.